Дневник свекрови: [роман] / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2016)
Экземпляры: (20160713) / Инвентарный номер: 39413 / Цена: 261.54 / Авт.знак: М 54 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6